2018
DOI: 10.1186/s13019-018-0709-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of coronary territory on flow profiles of saphenous vein grafts

Abstract: BackgroundDiffering perfusion of the left and right ventricular coronary territory may influence flow-profiles of saphenous vein grafts (SVGs). We compared flow parameters, measured by transit-time flowmetry (TTFM), in left- and right-sided SVGs during coronary artery by-pass grafting (CABG).MethodsRoutine TTFM measurements were obtained in 167 SVGs to the left territory (55%) and 134 SVGs to the right territory (total of 301 SVGs in 207 patients). The four standard TTFM parameters, [mean graft flow (MGF), pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
(31 reference statements)
1
6
0
Order By: Relevance
“…That might explain worse OPCABG outcomes in the repeatedly emphasized critical role of surgeons' experience [Benedetto 2018]. Previous studies comparing differences in intraoperative flow profiles between OPCABG and CABG showed lower flow values in the OPCABG group [Amin 2018;Hassanein 2005]. Recent studies comparing flow profiles between arterial and venous grafts in the left coronary supply territory and between OPCABG and CABG correlate with our flow analyses [Amin 2019].…”
Section: E966supporting
confidence: 71%
See 1 more Smart Citation
“…That might explain worse OPCABG outcomes in the repeatedly emphasized critical role of surgeons' experience [Benedetto 2018]. Previous studies comparing differences in intraoperative flow profiles between OPCABG and CABG showed lower flow values in the OPCABG group [Amin 2018;Hassanein 2005]. Recent studies comparing flow profiles between arterial and venous grafts in the left coronary supply territory and between OPCABG and CABG correlate with our flow analyses [Amin 2019].…”
Section: E966supporting
confidence: 71%
“…Studies that have specifically looked at flow in left-sided versus right-sided grafts are scarce and have included cohorts of arterial and venous conduits. Therefore, the current evidence for a potentially clinically relevant difference is insufficient and conflicting [Amin 2018;Tokuda 2007;Kim 2005;Nordgaard 2009]. Since this study only describes perioperative flow profiles, these results do not reflect the long-term flow profile in either group.…”
Section: E966mentioning
confidence: 87%
“…Coronary artery bypass graft failure has been associated with the following: high fractional flow reserve (FFR) (which was also associated with high mean PI, probably due to competitive, antegrade flow from the native coronary artery); TTFM measurements in the early diastolic phase; smoothness of the graft‐flow curve for arterial grafts; and high PI and high systolic reverse flow . Published work from our group has shown that differences of TTFM parameters between left‐ and right‐sided vein grafts were small and unlikely to be of clinical relevance …”
Section: Discussionmentioning
confidence: 99%
“…Papaverine can be delivered by various ways, like injection into endothoracic fascia before LIMA dissection, pedicled perivascular injection, topical spray, and intraluminal administration with or without hydrostatic dilation. Few studies have shown that the intraluminal administration type of delivery improves LIMA flow very drastically [14] , but it is associated with mechanical injury to the lumen of the mammary artery causing dissections and medial disruption [9,10] . A study done by Hausmann [13] reported no difference in LIMA flow when papaverine was delivered intraluminally or injected in the pedicle after LIMA dissection.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, LIMA flow in Group 1 was statistically different from Group 2. Papaverine dosage used in the literature has varied from 0.3 mg/mL to 1.5 mg/mL and to a maximum of 50 mg [14] . We used papaverine with a 0.3 mg/ml concentration.…”
Section: Discussionmentioning
confidence: 99%